Psychological Treatments for People With Severe and Enduring Anorexia Nervosa: A Mini Review - Zhu, James; Yang, Yive; Touyz, Stephen; Park, Rebecca; Hay, Phillipa (Frontiers in Psychiatry, 2020)
This Mini-Review presents recent research into evidence for psychological treatments for people with severe and enduring anorexia nervosa (SEAN). Two psychological therapies, specialist supportive clinical management (SSCM) and cognitive behaviour therapy for anorexia nervosa (CBT-AN) have limited (one randomized controlled study) evidence of efficacy. Both had adaptations for SEAN, notably with revision of the primary treatment goal of improved quality of life and full weight recovery a secondary goal. A major issue with existing studies is poor definition of SEAN, and the large deficit in research that has used an agreed definition of SEAN. In particular, it may be problematic to extrapolate from studies of people with either severe and/or enduring but not intractable or ‘resistant’ illness. People with longstanding AN who have not received evidence based care should be offered this with an expectation of recovery. Similarly, people with SEAN may be offered care with judicious mitigation of expectations. In the future trials should include people with SEAN clearly defined. Trials where a subsample of participants is likely to have SEAN provide an opportunity for secondary analyses at the point of stratification during randomization, thus widening the evidence base for psychological treatments and provide hope for people enduring this devastating illness. Finally, there is an urgent need not only to strengthen our existing knowledge with studies of sufficient power, but also, fundamentally, to derive novel conceptualisations of what ‘treatment’ involves.